Influence of pH on the Thermal Inactivation Kinetics of Horseradish Peroxidase in Aqueous Solution - Lemos, Maria Adı́lia
The thermal inactivation of horseradish peroxidase in aqueous solution was studied in the pH range of 3.0 to 12.5, at temperatures ranging from 40 °C to 95 °C. The data were well fitted by a double exponential model. The enzyme showed highest stability around neutral pH and the stability was particularly decreased above pH 11. The z value of the less labile fraction at pH 11.5 to 12.5 (temperatures from 40 to 65 °C) and of the more labile fraction at pH 3–4 (temperatures from 65 to 85 °C) were close to 10 °C, making these systems suitable as time-temperature integrators for assessing microbial lethality in thermal processing of low-acid foods, particularly if they can be stabilized further without affecting their low z-value.